Gender Mainstreaming dalam Kebijakan Pencegahan Kekerasan Seksual di Transportasi Publik Massal (CV. Era Digital Nusantara, 2025)
Gender-based sexual violence in public mass transportation, particularly at the KRL Commuter Line in Jabodetabek, represents a critical human rights violation threatening women's mobility rights and socio-economic participation. This normative-empirical legal research examines implementation gaps between operational sexual violence prevention policies and the holistic protection mandate under Law No. 12 of 2022 on Sexual Violence Crimes (UU TPKS). Employing gender mainstreaming framework and Crime Pattern Theory, the study identifies three structural vulnerabilities: insufficient gender-responsive reporting mechanisms, limited effectiveness of situational crime prevention approaches, and absence of explicit sexual violence protection clauses in transportation sector regulations. This research employs doctrinal analysis of regulatory instruments, case law evaluation, and gap analysis methodology. Findings demonstrate that current KAI Commuter strategies, while well-intentioned, remain partial and situational. The study proposes a reconstructed policy model integrating the 3E Framework (Enforcement, Environment, Education) with gender focal point governance mechanisms and mandatory Ministerial Regulation revisions. Effective prevention requires shifting from physical segregation toward cultural transformation and robust accountability systems ensuring equitable mobility rights for women.